Theoretical and methodological notes on visual and audiovisual sources in researches on Life Stories and Self-referential Memorials - Maria Helena Menna Barreto Abrahão (Universidade Federal de Santa Maria, 2014)
The text explicits the reflection that bases the use of pictures, films and videofilms as sources in research on Life Stories and Self-re- ferential Memorials in Teachers' Education. After refering to the researches in which we use this support since 1988, we work with two complementary pairs of theoretical dimensions of narratives in visual and audiovisual sources and their use in such empirical rese- arch: subjectivity/truth and space/time. These dimensions are worked grounded in Barthes (1984) to propose an interpretative effort of these sources to understand the essence of photography according to the photographer and the essence of photography according to the photographed person concocted to the essence of photography according to the researcher. The Barthesian constructs studium and punctum are applied to reading the narratives of the filmic and pho- tographic material, reaching the more radical expression of the Bar- thesian puctum: real or representational death of the referent that serves the photos and movies. The discussion of these dimensions for the analysis of (audio) visual sources is complemented with the support of several other authors.